Post‐dental extraction bleeding: Emphasis on the diagnosis of rare coagulation disorders. Issue 9 (30th August 2021) - Shadamarshan R, Arunkumar; Sharma, Rohit; Pradhan, Ishan; Kumar, Pramod
Abstract: Disorders of the fibrin stabilizing and fibrinolytic pathway should be considered in patients with excessive postsurgical bleeding with normal screening tests of hemostasis. History, clinical assessment of the timing and severity of bleeding along with utilization of advanced tests such as global hemostasis assays and appropriate coagulation factor assays (especially FXIII) will aid in the diagnosis. Abstract : Disorders of the fibrin stabilizing and fibrinolytic pathway should be considered in patients with excessive postsurgical bleeding with normal screening tests of hemostasis. History, clinical assessment of the timing and severity of bleeding along with utilization of advanced tests such as global hemostasis assays and appropriate coagulation factor assays (especially FXIII) will aid in the diagnosis.